A polyamide composite material and its preparation method and application

By adding polyurethane to the MCA flame-retardant glass fiber reinforced polyamide material, the interface bonding force of the material is improved, and the problem of insufficient MCA flame-retardant performance in the prior art is solved, and a polyamide composite material with high glow wire characteristics and excellent mechanical properties is achieved.

CN114507441BActive Publication Date: 2025-04-29KINGFA SCI & TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202111599779.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-12-24
Publication Date
2025-04-29
Estimated Expiration
2041-12-24

AI Technical Summary

Technical Problem

The prior art is difficult to effectively improve the flame retardant performance of melamine cyanurate (MCA) in glass fiber reinforced polyamide materials, especially in the glow wire test (GWFI).

Method used

A certain amount of polyurethane is added to the MCA flame-retardant glass fiber reinforced polyamide material. The polyurethane forms chemical force with the polyamide resin and glass fiber to enhance the interface bonding force of the material and reduce the "wick effect" of the glass fiber.

Benefits of technology

The glow wire performance and mechanical properties of the material are significantly improved, so that the GWFI of polyamide composite materials can reach 960℃, and the tensile strength is improved to meet the demand for high-performance materials in the electronic and electrical fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114507441B_ABST
    Figure CN114507441B_ABST
Patent Text Reader

Abstract

The invention discloses a polyamide composite material, which comprises components by weight: 38-90 parts of polyamide resin; 5-40 parts of glass fiber; 5-25 parts of melamine cyanurate; and 0.4-2 parts of polyurethane. The invention adds a certain amount of polyurethane to the MCA flame-retardant glass fiber reinforced polyamide material system. Due to the strong polarity of the polyurethane molecular chain segment, it can be used as a "connecting bridge" between the polyamide resin and the glass fiber, improve the interfacial bonding force between the glass fiber and the polyamide resin, and effectively reduce the "candle wick effect" of the glass fiber, so that the material has high glow-wire characteristics and excellent mechanical properties, which can meet the current demand for the use of materials in the field of electronic appliances, and is particularly suitable for the connector industry that has higher requirements for glow-wire performance and mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, and in particular to a polyamide composite material and a preparation method and application thereof. Background Art

[0002] Melamine cyanurate (MCA) is an important nitrogen-based flame retardant with the advantages of being halogen-free, low toxicity, and low smoke, and is particularly suitable for the flame retardancy of polyamide materials. However, for glass fiber reinforced polyamide materials, the "wick effect" of glass fiber will greatly reduce the flame retardant effect of MCA, making it difficult for the material to obtain good flame retardant properties.

[0003] In the field of electronics and electrical appliances, special attention is paid to the glow-wire performance of materials, especially in some products used in extreme environments (such as miniature circuit breakers MCB or contactors, etc.), and the high requirement that the material should reach the glow-wire test value (GWFI) of 960℃ and extinguish within 30s is proposed; and as people pay more and more attention to the environmental protection of products, the demand for high glow-wire halogen-free flame-retardant environmentally friendly materials in electronic and electrical products is increasing. Therefore, how to effectively improve the glow-wire performance of MCA flame-retardant glass fiber reinforced polyamide materials has become a research hotspot.

[0004] At present, the main method to improve the glow-wire performance of MCA flame-retardant glass fiber reinforced polyamide materials is to reduce the length of the glass fiber in the material, or to add a flame-retardant synergist. Chinese patent application CN110317450A discloses that in the MCA flame-retardant polyamide material system, glass fibers that have been calcined at high temperatures are used to make the glass fibers brittle and more easily ground to reduce the length when sheared by the extruder screw, thereby reducing the "wick effect" of the glass fibers and improving the glow-wire performance of the material; however, this technology requires the glass fibers to be pre-treated with high-temperature calcination for a long time, which greatly increases the processing steps and processing time, and increases the material processing cost. Chinese patent application CN112745675A compounds melamine cyanurate by adding methyl triallyl isocyanurate, which has good compatibility with melamine cyanurate, thereby improving the compatibility of melamine cyanurate in the matrix resin, improving the glow-wire performance of the material, and increasing the crystallization temperature and crystallization rate of the material, so that the material has better injection molding performance; however, this method has limited effect on improving the glow-wire performance of the material, and it is difficult to meet the high requirement of special electrical products that the material GWFI reaches 960°C. Summary of the invention

[0005] In order to overcome the above-mentioned deficiencies in the prior art, the object of the present invention is to provide a polyamide composite material with high glow-wire characteristics and excellent mechanical properties.

[0006] Another object of the present invention is to provide a method for preparing the polyamide composite material.

[0007] The present invention is achieved through the following technical solutions:

[0008] A polyamide composite material, comprising the following components by weight:

[0009] 38-90 parts of polyamide resin;

[0010] Glass fiber 5-40 parts;

[0011] 5-25 parts of melamine cyanurate;

[0012] Polyurethane 0.4-2 parts.

[0013] The present invention adds a certain amount of polyurethane to the MCA flame-retardant glass fiber reinforced polyamide material system. Since the polyurethane molecular chain segments contain abundant polar groups, they can simultaneously form chemical forces with the amide bonds of the polyamide resin and the Si-O bonds on the surface of the glass fiber, play a role in bridging the polyamide resin and the glass fiber, improve the interfacial bonding force between the glass fiber and the polyamide resin, and effectively reduce the "wick effect" of the glass fiber, thereby greatly improving the glow-wire performance of the material and significantly improving the tensile strength of the material.

[0014] The polyamide resin described in the present invention is derived from a dibasic acid monomer and a diamine monomer, or is derived from a lactam monomer, or is derived from an aminocarboxylic acid monomer, or is derived from two or more monomers of a dibasic acid, a diamine, a lactam, and an aminocarboxylic acid, and has an amide bond functional group; preferably, the polyamide resin is selected from any one or more of PA6 or PA66.

[0015] The polyurethane of the present invention is selected from any one or more of polyester thermoplastic polyurethane or polyether thermoplastic polyurethane. Preferably, the molecular weight of the polyurethane is 10,000-100,000; more preferably, the number average molecular weight of the polyurethane is 30,000-70,000.

[0016] Preferably, the length of the glass fiber is 1-6 mm; more preferably, the length of the glass fiber is 3-5 mm.

[0017] Preferably, the particle size D50 of the melamine cyanurate is less than 5 μm.

[0018] According to the material performance requirements, the polyamide composite material of the present invention further includes 0.1-2 parts of auxiliary agents by weight; the auxiliary agents include any one or more of antioxidants or lubricants.

[0019] The antioxidant includes but is not limited to any one or more of monophenol and bisphenol antioxidants, phosphite antioxidants, sulfur-containing antioxidants, amine antioxidants, and semi-hindered phenol antioxidants; such as the commonly used hindered phenol antioxidant N,N'-hexamethylenebis(3,5-di-tert-butyl-4-hydroxyphenylpropionamide).

[0020] The lubricant includes, but is not limited to, any one or more of ethylene bisstearamide, dimethyl silicone oil, stearic acid amide, stearic acid, butyl stearate, ester wax, saponified wax, such as the commonly used lubricant aluminum stearate.

[0021] The present invention also provides a method for preparing the polyamide composite material, comprising the following steps:

[0022] According to the ratio, each component is put into a mixer and mixed until uniform to obtain a premix; then the obtained premix is ​​put into a twin-screw extruder for melt mixing, and extruded into granules to obtain a polyamide composite material; wherein the screw aspect ratio of the twin-screw extruder is (40-48): 1, the barrel temperature is 200~275°C, and the screw speed is 250~500rpm.

[0023] The present invention also provides the application of the polyamide composite material in the connector industry, which can be specifically used in miniature circuit breakers MCB or contactors.

[0024] The present invention has the following beneficial effects:

[0025] The MCA flame-retardant glass fiber reinforced polyamide material of the present invention is added with a certain amount of polyurethane. The polyurethane acts as a "connecting bridge" between the polyamide resin and the glass fiber in the material, thereby improving the interface bonding force between the two and effectively reducing the "wick effect" of the glass fiber, so that the material has high glow-wire properties (GWFI can even reach 960°C) and excellent mechanical properties (high tensile strength), which can meet the current demand for the use of materials in the field of electronic appliances, and is particularly suitable for the connector industry that has higher requirements for glow-wire properties and mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is the SEM image of the cross section of the injection-molded polyamide composite material of Example 2.

[0027] Figure 2 This is the SEM image of the cross section of the injection molded polyamide composite material of comparative example 3. DETAILED DESCRIPTION

[0028] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.

[0029] The raw materials used in the embodiments and comparative examples of the present invention are described as follows, but are not limited to these materials:

[0030] Polyamide resin 1: PA66 EP-158, Zhejiang Huafeng Group;

[0031] Polyamide resin 2: PA6 HY-2500A, Jiangsu Haiyang Chemical Fiber Co., Ltd.;

[0032] Glass fiber 1: 3.5 mm in length, ECS10-03-568H, Jushi Group Co., Ltd.

[0033] Glass fiber 2: length 1.7 mm, ECS301CL-1.7-H, Chongqing International Composite Materials Co., Ltd.;

[0034] Glass fiber 3: Length 20 mm, glass fiber ER4301H-2400, Chongqing International Composite Materials Co., Ltd.

[0035] Melamine cyanurate 1: particle size D50 is 2.4 μm, melamine cyanurate MCA, Shouguang Weidong Chemical Co., Ltd. Flame Retardant Factory;

[0036] Melamine cyanurate 2: particle size D50 is 1.8 μm, nitrogen-based flame retardant lubricant MCA, Sichuan Fine Chemical Research and Design Institute;

[0037] Melamine cyanurate 3: particle size D50 is 15 μm, MCA-01, Sichuan Fine Chemical Research and Design Institute;

[0038] Polyurethane 1: polyester thermoplastic polyurethane, number average molecular weight 50000, HF-1065AP, Zhejiang Huafeng Thermoplastic Polyurethane Co., Ltd.;

[0039] Polyurethane 2: polyether thermoplastic polyurethane, number average molecular weight 50000, HF-4385AH-3, Zhejiang Huafeng Thermoplastic Polyurethane Co., Ltd.;

[0040] Polyurethane 3: polyether thermoplastic polyurethane, number average molecular weight 75000, HF-S4070A, Zhejiang Huafeng Thermoplastic Polyurethane Co., Ltd.;

[0041] Polyurethane 4: polyester thermoplastic polyurethane, number average molecular weight 11000, HF-1090AL-3, Zhejiang Huafeng Thermoplastic Polyurethane Co., Ltd.;

[0042] Epoxy resin: YD-019, Guodu Chemical (Kunshan) Co., Ltd.;

[0043] Antioxidant: hindered amine antioxidant, N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine, IRGANOX 1098, BASF;

[0044] Lubricant: External lubricant, stearyl stearate, LOXIOL G32, Koning, Germany.

[0045] Preparation methods of polyamide composite materials of embodiments and comparative examples:

[0046] According to the ratio in Table 1 / Table 2, each component is put into a mixer and mixed until uniform to obtain a premix; then the obtained premix is ​​put into a twin-screw extruder for melt mixing, and extruded into granules to obtain a polyamide composite material; wherein the screw aspect ratio of the twin-screw extruder is 48:1, the barrel temperature is 250℃-220℃-220℃-220℃-210℃-210℃-210℃-230℃-230℃-250℃, and the screw speed is 350rpm.

[0047] Related performance test methods:

[0048] (1) Glow wire test: Refer to standard IEC 60695, injection molded square plate specimens of 100*100*1.0mm, and test by gradually increasing the temperature. The initial test temperature is 700℃, and the temperature is gradually increased after the test passes.

[0049] (2) Tensile strength: Referring to the standard ISO 527-2-2012, the injection molded specimens were left to cool for 2 hours before testing; the tensile speed was 10 mm / min.

[0050] (3) SEM observation: Liquid nitrogen notched impact specimens were used to observe the microscopic morphology of the cross section using a scanning electron microscope (SEM). Figure 1 In the polyamide composite material to which 1.5 parts of polyurethane are added in Example 2, it can be observed that the surface of the glass fiber is rough and has a strong bonding force with the polyamide resin; Figure 2 For the polyamide composite material of comparative example 3 to which polyurethane is not added, it can be observed that the surface of the glass fiber is relatively smooth, and there is basically no mutual bonding force between the glass fiber and the polyamide resin; this indicates that the addition of polyurethane can play a role in bridging the polyamide resin and the glass fiber in the material, and can effectively improve the interfacial bonding force between the two.

[0051] Table 1: Distribution ratio of each group in Examples 1-6 (by weight) and related performance test results

[0052] Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Polyamide resin 1 60 60 60 60 60 60 Glass fiber1 30 30 30 30 30 30 Melamine cyanurate 1 10 10 10 10 10 10 Polyurethane 1 0.4 1.5 2 Polyurethane 2 1.5 Polyurethane 3 1.5 Polyurethane 4 1.5 Antioxidants 0.2 0.2 0.2 0.2 0.2 0.2 Lubricants 0.4 0.4 0.4 0.4 0.4 0.4 GWFI / ℃ 930 960 960 960 960 930 Tensile strength / MPa 82.7 84.5 84.9 85.1 83.6 82.9

[0053] Table 2: Distribution ratio of each group in Examples 7-13 (by weight) and related performance test results

[0054] Example 7 Example 8 Example 9 Example 10 Embodiment 11 Example 12 Embodiment 13 Polyamide resin 1 60 60 60 60 Polyamide resin 2 60 40 90 Glass fiber1 30 30 30 20 40 Fiberglass 2 30 Glass Fiber 3 30 Melamine cyanurate 1 10 10 10 8 Melamine cyanurate 2 10 15 Melamine cyanurate 3 10 Polyurethane 1 1.5 1.5 1.5 1.5 1.5 1.2 1.8 Antioxidants 0.2 0.2 0.2 0.2 0.2 / 0.2 Lubricants 0.4 0.4 0.4 0.4 0.4 / 0.4 GWFI / ℃ 960 960 930 960 900 930 960 Tensile strength / MPa 83.5 82.9 83.4 83.1 81.2 83.5 81.5

[0055] Table 2: Distribution ratios of each group in comparative examples 1-5 (by weight) and related performance test results

[0056] Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Polyamide resin 1 60 60 60 60 Polyamide resin 2 60 Glass fiber1 30 30 30 30 30 Melamine cyanurate 1 10 10 10 10 10 Polyurethane 1 0.2 3 / / Epoxy resin 1.5 Antioxidants 0.2 0.2 0.2 0.2 0.2 Lubricants 0.4 0.4 0.4 0.4 0.4 GWFI / ℃ 825 850 800 800 775 Tensile strength / MPa 81.4 82.7 75.2 72.6 78.2

[0057] It can be seen from the above embodiments and comparative examples that the present invention can significantly improve the glow-wire characteristics and mechanical properties of the material by adding a certain amount of polyurethane to the MCA flame-retardant glass fiber reinforced polyamide material system; the GWFI of the obtained polyamide composite material can reach 960°C and has a high tensile strength.

[0058] Compared with Example 2, in Comparative Example 1 / 2, the amount of polyurethane added is too little, and the improvement effect on the glow-wire properties of the material is not obvious, and the GWFI of the material is only 825°C; if the amount of polyurethane added is too much, the GWFI performance of the polyurethane itself is poor, which will reduce the glow-wire performance of the material.

[0059] In comparative example 3 / 4, no polyurethane is added, the GWFI of the material is only 800°C, and the tensile strength is relatively low.

[0060] In comparative example 5, the use of epoxy resin did not improve the glow-wire characteristics and mechanical properties of the material, but instead resulted in a decrease in the GWFI of the material.

Claims

1. A polyamide composite material, characterized in that: By weight, it includes the following components: 38-90 parts of polyamide resin; Glass fiber 5-40 parts; 8-25 parts of melamine cyanurate; Polyurethane 0.4-2 parts; The polyurethane is selected from any one or more of polyester thermoplastic polyurethane or polyether thermoplastic polyurethane, and has a number average molecular weight of 30,000 to 70,000; The length of the glass fiber is 1-3.5 mm, and the particle size D50 of the melamine cyanurate is ≤2.4 μm.

2. The polyamide composite material according to claim 1, characterized in that: The polyamide resin is derived from a dibasic acid monomer and a diamine monomer, or from a lactam monomer, or from an aminocarboxylic acid monomer, or from at least two monomers of a dibasic acid, a diamine, a lactam, and an aminocarboxylic acid, and has an amide bond functional group.

3. The polyamide composite material according to claim 1, characterized in that: The polyamide resin is selected from any one or more of PA6 or PA66.

4. The polyamide composite material according to claim 1, characterized in that: By weight, the invention further comprises 0.1-2 parts of auxiliary agent; the auxiliary agent is selected from at least one of an antioxidant or a lubricant.

5. The method for preparing the polyamide composite material according to any one of claims 1 to 4, characterized in that: The following steps are involved: According to the ratio, each component is put into a mixer and mixed until uniform to obtain a premix; then the obtained premix is ​​put into a twin-screw extruder for melt mixing, and extruded into granules to obtain a polyamide composite material; wherein the screw aspect ratio of the twin-screw extruder is (40-48): 1, the barrel temperature is 200~275°C, and the screw speed is 250~500rpm.

6. Application of the polyamide composite material according to any one of claims 1 to 4 in the connector industry.

Citation Information

Patent Citations

  • Halogen-free flame-retardant polyamide composite material as well as preparation method and application thereof

    CN112745675A

  • Reinforced and toughened weather-resistant and flame-retardant glass fiber reinforced PA66 electric power fitting material and preparation method thereof

    CN106566238A

  • Flame-retardant polyamide composition

    CN110317450A

  • Precipitation-resistant nitrogen flame-retardant nylon composite material prepared from waste fishing net wire reclaimed material

    CN111635628A

  • Blends that consist of TPU and polyamide

    CN113767132A